REPRESENTASI KELAS PEKERJA PADA IKLAN TELEVISI PT JAMSOSTEK (PERSERO) (Analisis Semiotika Iklan Televisi PT Jamsostek (Persero) Versi “Manfaat”) - Rina Wulansari; Saepudin . (Fakultas Komunikasi, Sastra, dan Bahasa, 2015)
Marketers often use television ad as for promoting their products. Representation, free play of sign, certain meaning always present on television commercial ad. Commercial ad of PT Jamsostek (Persero) version “Manfaat” is one of the commercial ad the representation. Commercial ad of PT Jamsostek (Persero) version “Manfaat” present representation of the working class. Purpose of this research is to know representation of the working class, sign, and certain meaning on television commercial ad PT Jamsostek (Persero) version “Manfaat”. Method of this research is descriptive qualitative research with Roland Barthes’s semiotic analysis approach. As a descriptive research, this research is only explain situation or discourse and it is not to in relationship, or do not to examine of hypothesis or to make a prediction. Analysis of data the researcher use is Roland Barthes’s semiotic approach which include signifier a meaningful of sound or meaningful scribbles, signified is a representation of mental or concept of something from signifier, denotation, and connotation. The signs on television commercial ad PT Jamsostek (Persero) version “Manfaat” oral, writing, and visual signs. The meaning of signs on this is the certain meaning of denotation and connotation. This commercial uses the denotation of meaning because it is want to know to the public in transparancy about the program as well as the advantage offered. This ad represents two class of labour, there are high class and low class